Pemantapan Keterampilan Dasar Mengajar Calon Guru Pendidikan Agama Islam dengan Pedagogi Multiliteracy pada Program Studi Pendidikan Agama Islam Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Muhammad Munib (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The teacher must control the environment as an important part of the process that occurs in the black box, it still must be an important part so that there is not one second that is not useful for the child, since they entered the school gate. Preparation in class, in class, rest periods and also their time at the house of worship, even when they are in the school canteen, are productive times to change their behavior, both ways of thinking, behaving and acting, or even increasing skills and their skills. Based on the focus of the study, this study aims to describe the strengthening of basic teaching skills of Islamic Religious Education teacher candidates with multiliteracy pedagogy in the Islamic Education Study Program at the Raden Wijaya Tarbiyah College of Education in Mojokerto. This research is